Investigation of Antimicrobial and Antioxidant Properties of Tamarix nilotica (Ehrenb.) Bunge Leaf Extract Against Catheter-Associated Urinary Tract Infections (CAUTIs) in Al Kharj Governorate - Muhammad Musthafa Poyil; Mohammed H Karrar Alsharif; Abdullah Mohammed Radwan Arafah (Journal of Pharmacy and Bioallied Sciences)
Introduction: One of most important nosocomial infections, Catheter associated urinary tract infections (CAUTI) are caused by many biofilms forming organism which makes treatment challenges as well as resistant strain development. To prevent the CAUTI, the new antimicrobials are needed immediately. Methodology: The overnight grown cultures such as S. aureus, P. aeruginosa, and C. albicans were grown in Brain Heart Infusion (BHI) broth, Mueller Hinton Broth (MHB), and Sabouraud Dextrose Broth (SDB). Ampicillin, rifampicin, and nystatin were used in all the experiments as positive controls and also, methanol was used as vehicle control. Results: The T. nilotica leaf extract showed antimicrobial activity at 2 mg/ml against S. aureus and 1 mg/ml against P. aeruginosa and C. albicans. Further, crystal violet staining revealed, T. nilotica antibiofilm activity through biofilm inhibition and also, it was efficiently eliminated 77%, 73%, and 78% of S. aureus, P. aeruginosa and C. albicans mature biofilms individually. Later, catheter coating with leaf extract explored strong antimicrobial activity against tested pathogens in in vitro bladder model. In addition, T. nilotica leaf extract expressed strong antioxidant property. Conclusion: T. nilotica can be considered as alternative antimicrobial agent for CAUTI treatment.